2021
DOI: 10.1097/cpt.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

Condensed Outpatient Rehabilitation Early After Lung Transplantation: A Retrospective Analysis of 6-Minute Walk Distance and Its Predictors

Abstract: The objectives were to evaluate the effect of a condensed post-lung transplant outpatient rehabilitation program started immediately after hospital discharge on 6-minute walk distance (6MWD) and to explore predictors of change in 6MWD and time to complete rehabilitation. Methods: Data were retrospectively collected from July 2009 to February 2019 on recipients who completed physical therapy-based posttransplant outpatient rehabilitation (PTOR). Changes in 6MWD prerehabilitation to postrehabilitation were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 31 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…The current study reports significant gains in endurance (6MWD) of up to 91%, the closest to healthy performance that has been described in a 5-day per week postoperative outpatient rehabilitation program. 16 Although previous reports of endurance recovery range from 65% to 85% by 3 months after transplant, 3,12,13,25 data from the same center before the COLTT program reported recovery of 6MWD from 82% to 85% at 6 and 12 months after transplant. 25 Walsh et al 12 reported a 3% to 66% recovery in 6MWD in the first 6 weeks after transplant and suggested the inconsistent gains are due to the variation among rehabilitation programs.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The current study reports significant gains in endurance (6MWD) of up to 91%, the closest to healthy performance that has been described in a 5-day per week postoperative outpatient rehabilitation program. 16 Although previous reports of endurance recovery range from 65% to 85% by 3 months after transplant, 3,12,13,25 data from the same center before the COLTT program reported recovery of 6MWD from 82% to 85% at 6 and 12 months after transplant. 25 Walsh et al 12 reported a 3% to 66% recovery in 6MWD in the first 6 weeks after transplant and suggested the inconsistent gains are due to the variation among rehabilitation programs.…”
Section: Discussionmentioning
confidence: 95%
“…This represents a more timely functional recovery than previously reported. 13,16,25 It is unclear which components of the program resulted in the accelerated recovery experienced by the participants; however, the finding that strength changes (1-minute sit to stand) are correlated with endurance changes (6MWD) suggests the addition of strength training may be a factor. Other studies have shown this correlation in healthy adults, patients with COPD, lung transplant candidates, and lung transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations